Trace Minerals in Growth, Production and Reproduction in Farm Animals - Kumar, Rajesh; Singh, Kunwar Dhananjay; Chauhan, Shailendra Singh; Verma, Manoj Kumar; Verma, Ajeet Kumar; Singh, Jaswant; Srivastva, Sushant; Kumar, Pramod (The Indian Journal of Animal Reproduction, 2025)
Inorganic minerals play a critical role in various physiological processes like growth, production and reproduction of animals. Requirements of minerals vary with different physiological states such as age, parity, stage of pregnancy (early vs advanced pregnancy) and stage of lactation i.e. non-lactating or lactating, production status as well as extent of minerals absorption by the body. The classification of minerals is based on their requirements in the animal body. The minerals required in much smaller amounts are referred to as trace or micro minerals i.e. cobalt (Co), Iron (Fe), Copper (Cu), Iodine (I), zinc (Zn), manganese (Mn), selenium (Se), molybdenum (Mo), chromium (Cr), and fluorine (F). In diet, the concentration of microminerals is expressed as ppm (parts per million), mg/kg (milligram per kilogram), whereas in some cases as ppb (parts per billion) or μg/kg (microgram per kilogram) of diet. The optimum amount of macro, as well as microminerals, is of utmost importance for various physiological needs. Deficiency and excess both have detrimental effects on growth, production and reproduction; thus have a significant bearing on the profitability of animal husbandry. Keywords: Bioavailability, Minerals, Livestock, Nutrition, Production, Reproduction.